2020
DOI: 10.1192/bjo.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Staff training in positive behaviour support for behaviour that challenges in people with intellectual disability: cost-utility analysis of a cluster randomised controlled trial

Abstract: Background Behaviour that challenges in people with intellectual disability is associated with higher healthcare, social care and societal costs. Although behavioural therapies are widely used, there is limited evidence regarding the cost and quality-adjusted life-years (QALYs). Aims We aimed to assess the incremental cost per QALY gained of therapist training in positive behaviour support (PBS) and treatment as usual (TAU) compared with TAU using data from a cluster randomised controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, clear evidence drawn from large randomised controlled trials is still lacking and the health economic evaluation of psychological interventions in the field of intellectual disabilities is in its infancy, with only a few studies including such approaches (Hunter 2020). Both of those are necessary conditions for the rollout of the interventions in intellectual disabilities services in the NHS and beyond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clear evidence drawn from large randomised controlled trials is still lacking and the health economic evaluation of psychological interventions in the field of intellectual disabilities is in its infancy, with only a few studies including such approaches (Hunter 2020). Both of those are necessary conditions for the rollout of the interventions in intellectual disabilities services in the NHS and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of NICE guidelines on interventions for challenging behaviour in people with intellectual disabilities (NICE 2015a), there is cautious optimism generated by emerging directions in understanding the underlying aetiologies of such behaviour and the relative proliferation of adapted or newly developed psychosocial therapies for its management. However, clear evidence drawn from large randomised controlled trials is still lacking and the health economic evaluation of psychological interventions in the field of intellectual disabilities is in its infancy, with only a few studies including such approaches (Hunter 2020). Both of those are necessary conditions for the rollout of the interventions in intellectual disabilities services in the NHS and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Following feedback from participants, we moved to the youth version of the EQ‐5D, the language of which they found easier to understand. A study in a more severe population found that the EQ‐5D‐Y was sensitive to changes in challenging behaviour, although this was predominately completed by proxies (Hunter et al, 2020). We, therefore, suggest the EQ‐5DY be considered for use in future studies with this population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, for individuals with intellectual disabilities, maintaining or improving upon their performance in the activities of daily life is difficult due to their various limitations, which may also affect their performance in the workplace [ 27 ]. As individuals with intellectual disabilities physically and mentally develop more slowly than those without intellectual disabilities, greater attention should be paid to their physical and mental health concerns [ 2 , 28 ]. Especially in adolescence, the lack of proper physical stimulation may inhibit the normal development of organs and tissues [ 29 ].…”
Section: Discussionmentioning
confidence: 99%